Secondary findings in 622 Turkish clinical exome sequencing data - ARMAN, AHMET; GÜNEY, AHMET İLTER; GEÇKİNLİ, BİLGEN BİLGE; ALAVANDA, CEREN; POLAT, HAMZA; ATA, PINAR (SPRINGERNATURE, 2021)
CES (Clinical Exome Sequencing) is a method that we use to diagnose rare diseases with nonspesific clinical features. Besides primary indication for testing genetic information may be detected about diseases which have not yet emerged. ACMG guidelines recommend to report pathogenic variations in medically actionable 59 genes. In this study we evaluated CES data of 622 cases which were tested for various indications. According to ACMG recommendations 59 genes were screened for reportable variations. The detected variations were reviewed using distinct databases and ACMG variation classification guidelines. Among 622 cases 13 (2.1%) had reportable variations including oncogenetic, cardiogenetic disorders, and malignant hyperthermia susceptibility-related genes. In 15 cases (2.4%) heterozygous pathogenic and likely pathogenic variations were detected in genes showing autosomal recessive inheritance. Ten novel variations causing truncated protein or splicing defect were reported. We detected 11 variations having conflicting interpretations in databases and 30 novel variations, predicted as likely pathogenic via insilico analysis tools which further evaluations are needed. As to our knowledge this is the first study investigating secondary findings in Turkish population. To extract the information that may lead to prevent severe morbidities and mortalities from big data is a valuable and lifesaving effort. Results of this study will contrbute to existing knowledge about secondary findings in exome sequencing and will be a pioneer for studies in Turkish population.
Keywords: ACMG RECOMMENDATIONS; INCIDENTAL FINDINGS; MEDICAL GENETICS; AMERICAN-COLLEGE; STANDARDS; UPDATE